EMPLOYEE PERCEPTIONS OF CORPORATE SOCIAL RESPONSIBILTY AND THEIR IMPACT ON ORGANISATIONAL COMMITMENT IN PAKISTAN - Pasha, Aneeqa (2022)
The concept and issue of corporate social responsibility (CSR) has grown increasingly divisive over the years. While a growing literature in the developed world has sought to address its importance and influence on organisational outcomes and different stakeholders, the subjective perceptions of employees have still not received great attention in general and especially in developing countries. This study seeks to contribute to an understanding of employees and their perspectives. These perspectives and motivations are studied in relation to CSR practices and organisational commitment in Pakistan. A qualitative, social constructivist approach is taken to examine which factors influence an employee’s commitment to the organisation and if CSR is one of them. The study highlights how important context is when thinking about CSR as a motivator because while someone in America might only apply and work for companies that match their personal values, someone in Pakistan might not be able to make the same choice due to different prevailing circumstances.